2020
DOI: 10.1038/s41467-020-16909-y
|View full text |Cite
|
Sign up to set email alerts
|

Deazaflavin reductive photocatalysis involves excited semiquinone radicals

Abstract: Flavin-mediated photocatalytic oxidations are established in synthetic chemistry. In contrast, their use in reductive chemistry is rare. Deazaflavins with a much lower reduction potential are even better suited for reductive chemistry rendering also deazaflavin semiquinones as strong reductants. However, no direct evidence exists for the involvement of these radical species in reductive processes. Here, we synthesise deazaflavins with different substituents at C5 and demonstrate their photocatalytic activity i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
7

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 73 publications
1
53
0
7
Order By: Relevance
“…A self‐constructed Time Correlated Single Photon Counting (TCSPC) setup [16h,30] was used to record emission decay data at single detection wavelength. A quartz cuvette with four optical windows of the dimension 2 mm×10 mm was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A self‐constructed Time Correlated Single Photon Counting (TCSPC) setup [16h,30] was used to record emission decay data at single detection wavelength. A quartz cuvette with four optical windows of the dimension 2 mm×10 mm was used.…”
Section: Methodsmentioning
confidence: 99%
“…The ns to ms transient absorption spectroscopy was recorded by a streak camera setup as described previously [16h,21a,30–31] . In brief, the third harmonic of a Nd : YAG laser (10 Hz, Surelite II, Continuum) pumping an Optical Parametric Oscillator (OPO, Continuum) tuned to 355/460 nm (10 mJ, ca .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…64 In 2020, König, Cibulka, Kutta, and co-workers reported deazaflavin 24, which was successfully applied in one-electron reductions under irradiation resulting in dehalogenation of aryl halide substrates (Scheme 18A). 65 These results are remarkable since their benchmark substrate 4-bromoanisole is very resistant towards reduction: E red = -2.75 V (vs. SCE). In a very detailed spectro-electrochemical study, it was shown that the active catalyst species is the photoexcited semiquinone 25* (Scheme 18B), which is a very strong reductant E* = -3.3 V (vs. SCE).…”
Section: Short Review Synthesismentioning
confidence: 97%
“…[5][6][7][8] This photoexcitation process has been exploited in a number of photocatalytic applications, whereby modification of the flavin chromophore can enable the formation of high potential oxidative and reductive intermediates to afford useful synthetic methodology. [9][10][11] Another application in which photoexcitation is utilised to generate reactive intermediates is within photodynamic inactivation (PDI) of pathogens. In this technique, a photosensitiser (PS) such as riboflavin, is employed to generate a burst of reactive oxygen species (ROS) in the vicinity of a particular pathogen in order to cause irreversible damage that leads to inactivation.…”
Section: Introductionmentioning
confidence: 99%